Breaking the Chain of Early Childhood Caries Transmission - Maxine Strickland; Kenneth Markowitz (Wolters Kluwer Medknow Publications, 2011)
Dental disease can have devas-tating effects on children who lack access to dental care. The US was shocked to learn of the recent death of a child from a caries related infection. The bio-logical basis of dental caries risk is usually considered interims of individual behavior. The role of the family and other more complex units of social organization in determining caries risk are not often appreciated. The transmission of caries causing bacteria from mothers (or other care givers having extensive contact with the child) has been well docu-mented. In addition the age at which children are vulnerable to colonization with caries causing organisms is known. Despite the fact that the dental and scientific communities possess knowledge concerning the routs of caries transmission, efforts to implement preventive programs specifically targeting the reduction of caries transmission have been inconsistent. Working with and motivating families to prevent caries transmission should be the shared objective of researchers and clinicians. Armed with the available know-ledge, caries should not the thought of as an inevitable part of life. The goal of this essay is to challenge readers to empower people at risk to make decisions that enable them to break the chain of caries infection.